Maternal binge alcohol consumption leads to distinctive acute perturbations in embryonic cardiac gene expression profiles. (22nd June 2022) - Abraham, Shani; Lindo, Chad; Peoples, Jessica; Cox, Amanda; Lytle, Erika; Nguyen, Vu; Mehta, Meeti; Alvarez, Jose D.; Yooseph, Shibu; Pacher, Pal; Ebert, Steven N.
Abstract: Background: Excessive alcohol consumption during pregnancy is associated with high risk of congenital heart defects, but it is unclear how alcohol specifically affects heart development during the acute aftermath of a maternal binge drinking episode. We hypothesize that administration of a single maternal binge dose of alcohol to pregnant mice at embryonic day 9.5 (E9.5) causes perturbations in the expression patterns of specific genes in the developing heart in the acute period (1–3 days) following the binge episode. To test this hypothesis and identify strong candidate ethanol‐sensitive target genes of interest, we adapted a mouse binge alcohol model that is associated with a high incidence of congenital heart defects as described below. Methods/Results: Pregnant mice were administered a single dose of alcohol (2.5 g/kg in saline) or control (saline alone) via oral gavage. To evaluate the impact of maternal binge alcohol on cardiac gene expression profiles, we isolated embryonic hearts from both groups ( n  = 5/group) at 24, 48, and 72 h post‐gavage for transcriptomic analyses. RNA was extracted and evaluated using quantitative RNA‐sequencing (RNA‐Seq) methods. To identify a cohort of binge‐altered cardiac genes, we set the threshold for change at >2.0‐fold difference with adjusted p  < 0.05 versus control.  RNA‐Seq analysis of cardiac gene expression revealed that of the 17 genes that were altered within the first 48 h post‐binge, with the largest category consisting of transcription factors ( Alx1, Alx4, HoxB7, HoxD8, and Runx2 ), followed by signaling molecules ( Adamts18, Dkk2, Rtl1, and Wnt7a ). Furthermore, multiple comparative and pathway analyses suggested that several of the candidate genes identified through differential RNA‐Seq analysis may interact through certain common pathways. To investigate this further, we performed gene‐specific qPCR analyses for three representative candidate targets: Runx2, Wnt7a, and Mlxipl . Notably, only Wnt7a showed significantly ( p  < 0.05) decreased expression in response to maternal binge alcohol in the qPCR assays. Conclusions: These findings identify Wnt7a and a short list of potential other candidate genes and pathways for further study, which could provide mechanistic insights into how maternal binge alcohol consumption produces congenital cardiac malformations. Abstract : To determine the underlying mechanisms mediating alcohol (EtOH) effects in the embryonic heart that have previously been associated with increased incidence of congenital heart defects, we performed RNA sequencing (RNA‐Seq) of embryonic heart samples 24–72 h post‐binge EtOH versus normal saline control administered via oral gavage at embryonic day 9.5 (E9.5). Our results show that Wnt7a and related signal transduction gene pathways were significantly decreased following maternal binge EtOH, thereby suggesting that disruption of these pathways may contribute to congenital defects.